2021
DOI: 10.3390/microorganisms9030490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Three Pseudomonas Species Isolated from the Eastern Oyster (Crassostrea virginica) Tissues, Mantle Fluid, and the Overlying Estuarine Water Column

Abstract: The eastern oysters serve as important keystone species in the United States, especially in the Gulf of Mexico estuarine waters, and at the same time, provide unparalleled economic, ecological, environmental, and cultural services. One ecosystem service that has garnered recent attention is the ability of oysters to sequester impurities and nutrients, such as nitrogen (N), from the estuarine water that feeds them, via their exceptional filtration mechanism coupled with microbially-mediated denitrification proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Although P. otitidis was initially isolated from a patient with an ear infection, this species is also widespread in nonclinical environments, as was MrB4, isolated from the near-shore area of Lake Biwa in Japan [73]. In agreement with these results, a recent study showed that a pair-wise comparison of P. alcaligenes OT69 against several type-strain genomes indicated P. otitidis DSM 17224 as its closest relative, rather than the type P. alcaligenes strain NBRC 14159, suggesting that OT69 should be included in a potentially new species [74]. In addition, these authors reported that P. alcaligenes OT69 and the other two oyster-associated Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 62%
“…Although P. otitidis was initially isolated from a patient with an ear infection, this species is also widespread in nonclinical environments, as was MrB4, isolated from the near-shore area of Lake Biwa in Japan [73]. In agreement with these results, a recent study showed that a pair-wise comparison of P. alcaligenes OT69 against several type-strain genomes indicated P. otitidis DSM 17224 as its closest relative, rather than the type P. alcaligenes strain NBRC 14159, suggesting that OT69 should be included in a potentially new species [74]. In addition, these authors reported that P. alcaligenes OT69 and the other two oyster-associated Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 62%
“… 80 Our previous studies along with several others have demonstrated pseudomonads to be a major bacterial group in the oysters. 44 , 45 , 46 Notably, some pseudomonads can be opportunistic pathogens and have been found in spoiled oysters. 1 , 53 , 81 To provide further insights into the metabolic traits of Pseudomonas species from the eastern oysters, we conducted whole genome sequencing (WGS), comparative genomic analysis and BIOLOG-based physiological assessments on isolates obtained from the eastern oysters.…”
Section: Resultsmentioning
confidence: 99%
“…were found to be the dominant oyster-associated bacteria. 43 , 44 , 45 , 46 More recently, our metagenomics survey of the eastern oysters indicated the dominance of Lactobacillus, Burkholderia , Bradyrhizobium , Afipia, and Delfitia bacterial groups with lower representations of Psychrobacter spp. Additionally, Mycoplasma , which has been previously suggested as one of the autochthonous bacteria in eastern oysters, was also identified (unpublished data).…”
Section: Introductionmentioning
confidence: 92%
“…One reason for the interest in the denitrification potential of bacteria associated with the Eastern oyster is that oyster aquaculture is associated with low greenhouse gas emissions [38]. Metagenomics sequencing technologies have aided in the identification of archaea and bacteria associated with oyster anatomical parts including the gills, gut, hemolymph, mantle, pallial fluid, stomach, and shell [37,[39][40][41][42][43]. In studies with a focus on the denitrification potential of the oyster microbiome [37,42], the bacteria genera identified include Clostridium, Endozoicomonas, Erythrobacter, Mycoplasma, Neptunibacter, Pleurocapsa, Psychrobacter, Pseudomonas, Pseudoalteromonas, Shewanella, Synechococcus, and Vibrio.…”
Section: Introductionmentioning
confidence: 99%